Development of expert system for bus services in Klang valley - Norhisham S.; Bakar M.F.A.; Syamsir A.; Zaini N.; Baharin N.L.; Shkuri N.S.M.; Saad N.M. (IOP Publishing Ltd, 2023)
Bus transportation; Buses; Developing countries; Disasters; Expert systems; Landforms; Quality of service; Expert system development; Major cities; Public transport; Public transportation; Specific location; Transit capacity; Transport systems; Transportation engineering; Information management